Investigation of Factors Influencing the Construction Safety of High-Speed Railway Stations Based on DEMATEL and ISM. (12th June 2021) - Lin, Feng; Wu, Ping; Xu, Yidong
Abstract : To explore the influencing factors and mutual influence mechanism of the construction safety of China's high-speed railway stations, this study takes the Hanghuang high-speed railway Fuyang station as the subject and studies 17 risk factors in 4 categories affecting construction safety based on system safety theory, and the interaction relationship and degree among the factors were analysed. Based on DEMATEL (Decision-making Trial and Evaluation Laboratory) and ISM (Interpretative Structural Modelling) methods, through a questionnaire survey, the logical relationship among the influencing factors is quantified. Then, the influencing degree, influenced degree, centrality, and causality of the influencing factors were calculated, and a multilevel hierarchical hybrid model is established to systematically analyse the influencing factors and the mechanism of high-speed railway station construction. The results show that the factors of construction safety risk are summarized as 3 main factors, 6 important factors, and 7 direct factors and personnel factors and management factors need to be controlled with emphasis. In addition, some measures are proposed. This research provides a theoretical basis and method for preventing accidents and improving the safety of high-speed railway station construction.